KEPUTUSAN BERKUNJUNG DI TRANSERA WATERPARK BEKASI: PERLUKAH MEMPERHATIKAN FASILITAS DAN HARGA? - Puspa RizkautamI; Revalino Tigor Hasudungan; Lenny Yusrini (Eduturisma, 2020)
Transera WaterPark is a recreational theme park located in Bekasi. In order to achieve sustainability, Transera WaterPark needs to implement a good strategy to understand the visitor’s needs. In this regard, this study aimed to explore how facilities and price-as parts of the marketing mix-influence visiting decision. The study’s sample is the visitors of Transera WaterPark Bekasi using accidental sampling. By using descriptive method and multiple linear analysis, this study found that facilities and price contributed 67.1% towards the decision to visit Transera WaterPark. The results of this study suggested that the management needs to add public facilities, and give more alternatives on the dry park’s vehicles. In regards to price, it is suggested to have pricing determination